Pengaruh Model Discovery Learning Terhadap Hasil Belajar Kelas XI MIA Pada Materi Sistem Pertahanan Tubuh Manusia Di SMA Negeri 1 Amfoang Barat Laut - Alexander Wungubelen; Aloysius Djalo; Florentina Yasinta Sepe (JBIOEDRA: Jurnal Pendidikan Biologi, 2023)
The use of the discovery learning model at SMA Negeri 1 Amfoang Utara has been implemented by biology subject teachers, but student learning outcomes are still brought to KKM standards, this is caused by the lack of enthusiasm of students in learning so that it influences student learning outcomes. Therefore, to improve student learning outcomes, teachers act as guides by providing opportunities for students to learn actively and directing student learning activities in accordance with learning objectives, using the discovery learning model. discovery learning model, able to increase student activity in the classroom. The aim of this research is to determine the effect of the discovery learning model on the learning outcomes of class XI MIA students at SMA Negeri 1 AMFOANG NORTHWEST KUPANG DISTRICT for the 2022/2023 academic year. The type of research used is quantitative research with quasi-experimental methods. The population in this study were all students in class XI MIA at SMA Negeri 1 AMFOANG NORTHWEST KUPANG DISTRICT, with the research sample consisting of classes XI MIA1 and XI MIA2. The data analysis technique in this research uses descriptive analysis and inferential analysis. The research results showed that the average learning outcomes of students in the experimental class obtained a pretest score of 44.45, increasing to 84.09 after being given the posttest. Meanwhile, in the control class, the pretest score was 45.00, increasing to 77.88 after being given the posttest. The number of students who completed in the experimental class was 87.87% and those who did not complete was 12.12%. In the control class the number of students who completed was 66.66% and those who did not complete was 33.33%. Based on the results of the one-way anacova test, a probability value (sig) of 0.004 was obtained, which was smaller than the set value, namely 0.05. This shows that Ha (the discovery learning model has an effect on student learning outcomes) is accepted and H0 (the discovery learning model has no effect on student learning outcomes) is rejected. Based on the research results and discussion of the data obtained, it can be concluded that the discovery learning model influences the learning outcomes of class XI MIA students on the human body defense system material The human body's defense system at SMA Negeri 1 Amfoang northwest Kupang district